2013
DOI: 10.1042/bj20130833
|View full text |Cite
|
Sign up to set email alerts
|

The miR-19a/b family positively regulates cardiomyocyte hypertrophy by targeting atrogin-1 and MuRF-1

Abstract: Progressive cardiac hypertrophy owing to pathological stimuli, such as pressure overload, is frequently associated with the development of heart failure, a major cause of morbidity and mortality worldwide. Growing evidence has shown that miRNAs are extensively involved in the pathogenesis of cardiac hypertrophy. In the present study, we examined the hypothesis that the miR-19a/b family acts as a key regulator of cardiac hypertrophy and apoptosis. Forced overexpression of miR-19a/b was sufficient to induce hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 42 publications
3
54
0
Order By: Relevance
“…For measuring Nuclear Factor of Activated T-cell (NFAT) activity, NFAT-luciferase assays were performed as described previously with minor modifications [14]. Briefly, 9xNFAT-luciferase reporter plasmid and pRL-TK containing the Renilla luciferase gene were cotransfected into NRVMs 24 h after transfection of NC inhibitor or miR-185 inhibitor.…”
Section: Methodsmentioning
confidence: 99%
“…For measuring Nuclear Factor of Activated T-cell (NFAT) activity, NFAT-luciferase assays were performed as described previously with minor modifications [14]. Briefly, 9xNFAT-luciferase reporter plasmid and pRL-TK containing the Renilla luciferase gene were cotransfected into NRVMs 24 h after transfection of NC inhibitor or miR-185 inhibitor.…”
Section: Methodsmentioning
confidence: 99%
“…miR-19b is a member of the miR-17-92 cluster (miR-17/18a/19a/19b/20a/92a), which is located on chromosome 13 [22,23]. Previous studies have shown that miR-19b is involved in aging-associated heart failure and the positive regulation of cardiomyocyte hypertrophy and apoptosis by targeting atrogin-1 and MuRF-1 [24]. As a potential plasma biomarker for the diagnosis of acute pulmonary embolism, miR-134 is also reported to be up-regulated in patients with acute coronary syndrome (ACS) [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a PKC inhibitor alone was able to restore the inflammatory response against UPEC. It has already been shown that CsA and the PKC inhibitor GF10923X antagonise the effects of the miR-19 family, regulating phenotypes of cardiomyocytes via the suppres-sion of multiple direct target genes [40]. Moreover, several signaling pathways activated during UPEC infection, including the pathways known to activate the innate immune response, interact with calcium-dependent signaling pathways.…”
Section: Discussionmentioning
confidence: 99%